Self-enhancement processing in the default network: a single-pulse TMS study - Luber, Bruce; Lou, Hans C.; Keenan, Julian P.; Lisanby, Sarah H. (Experimental brain research, 2012)
Much research has been done on positive self-evaluation and its relationship to mental health. However, little is known about its neural underpinnings. Imaging studies have suggested that the brain’s default network is involved with self-related processing and that one portion of the default network, medial prefrontal cortex (MPFC), is particularly involved with self-evaluation. Here, we used transcranial magnetic stimulation (TMS) to causally demonstrate that this network, and particularly MPFC, is involved with self-evaluative processing. In a first experiment, 27 healthy volunteers judged whether adjectives, evenly divided between desirable and undesirable traits, described themselves or their best friends, and a robust self-enhancement bias effect was found. In a second experiment, single-pulse TMS was applied targeting three locations (MPFC and left and right parietal cortex) in a different group of healthy volunteers while they performed the adjective task. In each trial, TMS was applied at one of five different times relative to onset of the adjective ranging from 0 to 480 ms. TMS affected self-enhancement bias in a site- and latency-specific manner: at MPFC, the self-enhancement bias actually reversed at 160 ms, with subjects favoring their best friend over themselves. TMS may thus be of use in investigating areas of mental illness in which self-evaluation is abnormal, potentially as a diagnostic tool. In addition, the present study, combined with our previous reports (Lou et al., Proc Natl Acad Sci USA 101(17):6827–6832, 2004 , Exp Brain Res 207:27–38, 2010 ), causally demonstrates two kinds of self-related processing within the default network, one centered in parietal cortex and concerned with retrieval of self-related associations, and the other MPFC-centered and involved in self-evaluative processing.